Secular trends in the grip strength and body mass index of sport university students between 1973 and 2016: J-Fit＋study - Tetsuhiro Kidokoro; Yoshimitsu Kohmura; Noriyuki Fuku; Yuki Someya; Koya Suzuki (Elsevier, 2020)
Background/Objective: Sport university students are a unique population because they usually have a strong sport background since early childhood. In this study, we aimed to examine secular trends in grip strength of male, first-year sport university students in comparison with the general population between 1973 and 2016. Methods: Existing data on the grip strength of 6,308 sport university students aged 18 years were examined. The data were obtained from the Juntendo Fitness Plus Study, a study of the Department of Physical Education/Health and Sports Science of Juntendo University. For reference, age- and sex-matched data (18 years old, male) on the grip strength were obtained from a national database. Results: Compared with the general population, the sport university students had greater body mass index and stronger grip strength at all times. Conclusions: The grip strength of sport university students significantly declined between the 1980s and 1990s, and it has plateaued since 2000, albeit at low levels. Compared with the peak performance of sport university students in 1984, the grip strength of students in 2016 was significantly lower by 8.1 kg. The downward trends were also confirmed in the general population during the same periods. In conclusion, the grip strength of sport university students has significantly declined over the last few decades. Keywords: Body size, College student, Japanese, Muscular fitness, Temporal changes, Young people